Поиск аномалий во временных рядах на основе оценивания их параметров - Мельникова, П. А. (ХНУРЕ, 2021)
Anomaly detection in every domain is an important topic of discussion and the knowledge about the effective ways to perform anomaly detection is an important skill to have for any Data Scientist. A problem of anomaly detection in time series is considered. A method is proposed, which allows to detect anomalies in time series efficiently by their parameters.
Keywords: временной ряд; поиск аномалий; метод кластеризации DBSCAN